Ghrelin receptor signaling is not required for glucocorticoid-induced obesity in female mice. Issue 2 (28th June 2021) - Silver, Zachary; Abbott-Tate, Sam; Hyland, Lindsay; Sherratt, Frances; Woodside, Barbara; Abizaid, Alfonso
Abstract : Chronic exposure to high circulating glucocorticoid or ghrelin concentrations increases food intake, weight gain and adiposity, suggesting that ghrelin could contribute to the metabolic effects of chronic glucocorticoids. In male mice, however, blocking ghrelin receptor (GHSR) signaling increased the weight gain and adiposity induced by chronic corticosterone (CORT), rather than attenuating them. In the current study, we investigated the role of GHSR signaling in the metabolic effects of chronic exposure to high circulating CORT in female mice. To do this, female WT and GHSR KO mice were treated with either CORT in a 1% ethanol (EtOH) solution or 1% EtOH alone in their drinking water for 32 days ( n  = 5–8/group). Body weight, food, and water intake as well as vaginal cyclicity were assessed daily. As expected, CORT treatment-induced significant increases in body weight, food intake, adiposity and also impaired glucose tolerance. In contrast to results observed in male mice, WT and GHSR KO female mice did not differ on any of these parameters. Neither plasma levels of ghrelin, LEAP-2, the endogenous GHSR antagonist produced by the liver, nor their ratio were altered by chronic glucocorticoid exposure. In addition, CORT treatment disrupted vaginal cyclicity, produced a reduction in sucrose consumption and increased locomotor activity regardless of genotype. Chronic CORT also decreased exploration in WT but not GHSR KO mice. Collectively, these data suggest that most metabolic, endocrine, reproductive and behavioral effects of chronic CORT exposure are independent of GHSR signaling in female mice.